Commissions for border waters and their role in the development of tourism. – on the example of Poland with particular emphasis on the southern border - Sanetra-Półgrabi, Sabina (Scientific Journal of Bielsko-Biala School of Finance and Law, 2021)
The article analyzes the significance of the commission for border waters, characterizes their structure and role, paying particular attention to the working groups, their tasks and achievements. Using the case study as a research method and basing on the existing literature on the subject in the field of political and administrative sciences, security sciences and other related disciplines, the main tasks of selected entities and their impact on the development of tourism were determined. Based on the analysis of the content of the minutes of the meetings of the representatives of the Polish-Slovak Commission for Border Waters and the Polish-Czech Commission for Border Waters, as well as their working groups, key areas related to the tasks they undertook for the period 2017-2019 were selected. These included: flood protection, planning and monitoring activities, implementation of the provisions of the Water Framework Directive as well as initiating and improving bilateral cooperation. Then, these areas were linked with activities that contribute to the development of tourism and what potential effects they bring. The article also indicates the final conclusions